Sleep assessment in preterm infants: Use of actigraphy and aEEG - BEKİROĞLU, GÜLNAZ NURAL (My University, 2022)
Objective: Objective methods to monitor the sleep of preterm infants at the neonatal intensive care unit (NICU) are required to prevent potentially adverse neurodevelopmental outcomes. This study aimed to determine the concordance of actigraphy and amplitude-integrated electroencephalogram (aEEG) against gold standard direct observation (DO) in assessing sleep/wake states of typically developing preterm infants. Methods: This prospective observational study was conducted in a single center level III NICU. Sleep variables were measured using Philips Respironics Mini-Mitter® Actiwatch-2 for 24 h and compared with 8-h matched data of aEEG and DO. Sensitivity-specificity analysis, Cohen's kappa, prevalenceadjusted and bias-adjusted kappa (PABAK), and Bland Altman plots were generated. Results: Seventeen preterm infants were recruited. A total of 11252 epochs were studied. Sensitivity (86.4%), agreement rate (67.9%), and predictive value for wake (47.9%) for the actigraphy were highest at the automatic activity threshold whereas specificity (54.5%) and predictive value for sleep (75.5%) were highest at low threshold. The sensitivity of aEEG was 79.3% and the specificity was 54.3%. At all thresholds, the agreement was largely equivalent with low kappas (0.14e0.17) and PABAK coefficients (0.22e0.35) for actigraphy and DO. Moderate agreement was observed between aEEG and DO according to the PABAK coefficient (0.44). Mean differences in sleep parameters were not different between DO and aEEG as well as DO/aEEG and actigraphy at medium threshold (p > 0.05). Conclusions: Actigraphy at medium threshold can be used in depicting sleep in typically developing preterm infants at NICU. aEEG may be an alternative adjunctive method to actigraphy for the evaluation of sleep/wake states in the NICU setting
Keywords: Tıp; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyoistatistik ve Tıp Bilişimi; Medicine; Internal Medicine Sciences; Child Health and Diseases; Health Sciences; Fundamental Medical Sciences; Biostatistics and Medical Informatics; Klinik Tıp (MED); Klinik Tıp; TIBBİ BİLİŞİM; PEDİATRİ; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICAL INFORMATICS; PEDIATRICS; MEDICINE, GENERAL & INTERNAL; Genel Sağlık Meslekleri; Pediatri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Pediatri, Perinatoloji ve Çocuk Sağlığı; Dahiliye; Tıbbi Bilişim; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pediatrics; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Pediatrics, Perinatology and Child Health; Internal Medicine; Health Informatics; Family Practice; Medicine (miscellaneous); General Medicine